REMNANT OF THE DRYLAND COASTAL VEGETATION OF THE SONGKHLA LAKE BASIN, SONGKHLA, THAILAND - Anusit Cheechang; Kitichate Sridith (BIOTROPIA, 2025)
HIGHLIGHTSThis article identifies and characterizes three native plant communities in the Songkhla Lake Basin, highlighting their distinct species composition, coastal zonation patterns, and ecological value. It reveals high plant diversity across remnant dryland coastal habitats and documents key native species that define each community type. The study emphasizes the negative impacts of human activity and land policies on native vegetation and offers baseline floristic data that support conservation, ecological restoration, and sustainable land-use planning.ABSTRACTThe remnant dryland coastal vegetation of the Songkhla Lake Basin, Songkhla, Thailand, was investigated in this study. Twenty vegetation plots were established to represent each vegetation subtype. Using Braun-Blanquet cluster analysis and the Jaccard similarity index, the vegetation was classified into three distinct communities: (1) the Coastal Woodland Community, located farthest inland and dominated by Dipterocarpus alatus Symington; (2) the Coastal Scrub-Shrubby Tree Community, situated inland from the coastal zone, with Dipterocarpus chartaceus Symington, Neolitsea zeylanica (Nees & T. Nees) Merr., and Psychotria asiatica L. identified as dominant species; and (3) the Coastal Scrub Community, occurring near the shoreline and characterized by densely clustered vegetation dominated by Mischocarpus sundaicus Blume, Planchonella obovata (R.Br.) Pierre, and Vitex pinnata L. Vegetation profiles for each community were delineated. Significant degradation and decline of native plant communities in the Songkhla Lake Basin have been caused by conservation activities involving the introduction of fast-growing non-native species and by governmental land tax policies.